An Innovative Holistic Approach to an E-flow Assessment Model - Gorana Ćosić-Flajsig; Ivan Vučković; Barbara Karleuša (Civil Engineering Journal, 2020)
River water resources provide a wide range of necessary ecosystem services, including regulating, provisioning, supporting and cultural services. Ecosystem services are linked to an appropriate level of functionality of river water resource processes, which can be connected with river basin environmental objectives. Environmental objectives can be achieved only if appropriate flow and sediment regimes and related river morphology quality are guaranteed. The obligation to define environmental flow (E-flow) in the European Union Water Framework Directive European (WFD) is not explicit, and the implementation of the WFD is more focused on water quality. Considering the specific climatic, hydrographic and hydrological conditions and the definition of E-flow, each EU country has developed procedures for their investigation and determination. In the Republic of Croatia, no methodology has been elaborated, nor is there any legal regulation to define E-flow downstream of a dam or water intake site. This paper presents the significant pressures that have affected the transboundary rural Sutla River basin between Croatia and Slovenia. These pressures can cause changes in the hydrological regime and biological elements of water quality. The holistic approach defines the E-flow for a profile on the Sutla River by linking hydrological, morphological, and ecological characteristics based on the exploration of the Sutla River and its biological communities. The full implementation of a holistic approach and the transition to Level III of the E-flow definition requires the enhancement of exploratory hydrological and biological monitoring that enables the use of habitat modelling. Doi: 10.28991/cej-2020-03091611 Full Text: PDF